Building Trust Through Communication : Strengthening Auditor Competency in the Public Sector - Yulisfan Yulisfan; Muhammad Irsan Nasution (Proceeding of The International Conference on Business and Economics, 2024)
This study examines the relationship between communication and auditor competency within Indonesia's public sector, focusing on its impact on audit quality and governance. The research addresses the challenges faced by public sector auditors, such as resource limitations and stakeholder expectations, which demand a balance between technical expertise and effective communication. The study was conducted in North Sumatra Province, involving 130 auditors affiliated with the Aparat Pengawasan Intern Pemerintah (APIP) network. A structured survey was used to collect data, focusing on auditors' communication skills, technical proficiency, and ethical judgment. Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed for data analysis, allowing the evaluation of complex constructs like communication efficacy and competency. The findings reveal that effective communication positively impacts auditor competency, enhancing collaboration within teams, fostering stakeholder trust, and ensuring actionable outcomes from audits. The results underscore the necessity of refining communication strategies to address governance complexities and stakeholder demands. This study highlights the symbiotic relationship between communication and competency, providing actionable insights for improving audit processes in Indonesia's public sector. It offers a foundation for developing training programs and frameworks that align with the International Professional Practices Framework (IPPF) and modern technological advancements to elevate public accountability.